Ce/Sm co-doped hydroxyapatites: synthesis, characterization, and band structure calculation - Kaygili, Omer; Vural, Gulay; Keser, Serhat; Yahia, I. S.; Bulut, Niyazi; Ates, Tankut; Ince, Turan (Springer, 2021)
In this paper, Ce/Sm co-doped hydroxyapatites (HAps) were synthesized by a wet chemical route. The amount of Ce was kept at constant at the value of at.% 0.4, and the second dopant of Sm was used at different amounts of at.% 0, 0.6, 1.2, and 1.8, respectively. The effects of these co-dopants on the crystal structure, morphology, and thermal properties of HAp were determined experimentally using X-ray diffraction (XRD), scanning electron microscopy (SEM), differential thermal analysis (DTA), and thermogravimetric analysis (TGA). Furthermore, the band structure of the prepared samples was modeled theoretically using the quantum calculations of the density of states and band structure. A gradual increase from 26.56 to 36.23 nm in the crystallite size was observed. Although the amounts of the co-dopants of Ce and Sm did not affect the thermal stability and microstructure of HAp, its crystal structure-related parameters were affected by the amount of these co-additives. The partial substitution of both co-dopants was detected. The 0.4Ce-1.2Sm-HAp sample may be considered as the best crystal structure with a steady-state. It was seen that the band structure and density of states were also affected by these co-dopants. The bandgap value decreased gradually from 4.6078 to 4.0477 eV due to these dopants.
Keywords: Hydroxyapatite; Wet chemical method; Band structure; Density of states (DOS); X-ray diffraction (XRD); Morphology